Magical Realism and its European Essence - Asayesh, Maryam Ebadi; Arargüҫ Mehmet Fikret (Journal of History Culture and Art Research, 2017)
Magical realism is known with its oxymoronic characteristic, magic plus realism. It became known with the boom of the magical realist novel in the 1960s in Latin America and became globally recognized from 1980 onwards. However, it is mostly forgotten that it had started its journey from Europe. The term “magic realism” first appeared in German philosophy in 1798 in Novalis’ notebook. Then, it entered art criticism in 1925 through Roh’s essay and developed in Italy through by Bontempelli. Later, after transformation and formation, magical realism appeared in the novels as a popular mode first in Latin America and then worldwide. The present study charts the path and discusses the development of magical realism from its commencement in Europe. In addition to presenting the views of Novalis, Roh and Bontempelli on initiating the term, it compares their views to show what characteristic in their views inspires today’s magic realism.